The Breach of Sisterhood and Cultural Transformation in Chitra Banerjee Divakaruni’s The Vine of Desire - Parkavi, V (Journal of English Language and Literature (ISSN: 2368-2132), 2018)
Love, Kindness faithfulness and tolerance are widely recognized traits of feminine sensibility. Women have multifaceted personalities. Many are able to tune themselves according to the ambience they live. Chitra Banerjee Divakaruni throws light on immigrant women. She picturesquely portrays the South Asian women’s plight, violence and individuality in a foreign land. The reader may never miss to notice the autobiographical elements in her works. She never misses to take us to her hometown Kolkata in her works. Women and particularly immigrant women are vibrant in her novels. She never portrays women as a weak sex. They strive to establish their identity at home, work place and in a foreign land. Divakaruni vividly portrays how women have to undergo a sea of pain to carve her own identity in the midst of gender and race dominated society. This paper ponders the introversion of immigrant women in Chitra Banerjee Divakaruni’s “The Vine of Desire”